PENGEMBANGAN BUDAYA RELIGIUS DI SEKOLAH - Prasetya, Benny (EDUKASI: Jurnal Pendidikan Islam, 2014)
Development of religious culture in schools is a first step in instilling the values of religious education in everyday life. Habituation religious values in schools is expected to in crease and strength the value of unity,religious knowledge and religious cult of students. To implement the development of the religious culture in school sand strategies necessary steps that must be passed either at the level of values, practices and religious symbols. Thus the behavior and mentality needed coaching through civilize in religious being in the school community, families, and communities where the students live and interact.